Functional outcomes and safety of GreenLight photovaporization of the prostate in the high‐risk patient with lower urinary tract symptoms due to benign prostatic enlargement. Issue 1 (1st November 2019) - Barco‐Castillo, Catalina; Plata, Mauricio; Zuluaga, Laura; Santander, Jessica; Trujillo, Carlos Gustavo; Caicedo, Juan Ignacio; Serrano, Adolfo; Fernández, Nicolás; Azuero, Julián
Abstract: Aims: Photovaporization of the prostate (PVP) with GreenLight Laser is a surgical treatment for lower urinary tract symptoms. It is considered safe in elderly patients with comorbidities, however, the evidence is inconclusive. The objective of this study is to evaluate the efficacy and safety outcomes of PVP according to the American Society of Anesthesiologists Physical Status (ASAPS). Methods: A cohort of 675 patients who underwent PVP between 2012 and 2018 was evaluated. Patients were classified according to their ASAPS as low (I and II) and high risk (III and IV). Surgical characteristics and improvement of symptoms and Quality of Life (QoL) were evaluated. Results: The median age of high‐risk group was higher than low‐risk group. The high‐risk group had more history of anticoagulation, antiaggregation, urinary catheterization, urinary retention and urethral stricture. Longer times of hospitalization (23.7 [interquartile range IQR = 18.9‐41.35] vs 21.8 hours [IQR = 18.7‐26.6], P = .008) and catheterization (19.55 [IQR = 15.6‐35.57] vs 17.67 hours [IQR = 14.76‐22.5], P = .004) were found in the high‐risk group. Conversion and bleeding control were not different between groups. In the follow‐up, improvement of International Prostate Symptoms Score (IPSS) and QoL was significant in all patients when compared before and after surgery scores ( P < .001). There were no difference between groups for QoL, however, IPSS was lower for the low‐risk group (8 [IQR = 4‐14.5] vs 5 [2‐12], P = .001). Conclusion: PVP with GreenLight Laser is a safe and efficient procedure for all patients despite their comorbidities, with comparable middle‐term outcomes which makes it a standard treatment for the entire aging population, improving their QoL.